Produção, caracterização estrutural e propriedades de armazenagem de hidrogênio de ligas Mg-Zr - Strozi, Renato Belli (Universidade Federal de São Carlos, 2017)
Magnesium is considered a promising candidate in applications of storage hydrogen in the solid state, due, among other factors, to its low relative cost and high gravimetric capacity (7,6 wt%.). For magnesium, the use of transition metals as additives may show great improvements in the kinetics of hydrogen absorption/desorption. Different additives can have different functionalities, for example, reducing the energy barrier for H2 adsorption and acting as a heterogeneous nucleating agent in the kinetics of phase transformation. In this research, the main effects of the use of zirconium (Zr) as an additive of the magnesium for the purposes of hydrogen storage in bulks produced by rapid solidification in melt-spinning furnace and cold rolling were studied in detail. Basically, structural characteristics were related to the behavior of absorption / desorption. The alloy produced by cold rolling showed behavior of activation and absorption similar to the pure Mg which was produced by the same route. For the route processed by melt spinning, the use of zirconium as additive has presented a deleterious effect on the activation. However, after activation, the kinetics of absorption exhibit behavior similar to pure Mg. The activation had significantly improved after mechanical or thermal processing, however, the structural characteristics that permeate this effect still have a lack of studies. For both process route, the desorption kinetics presented excellent results, reducing the complete reaction in a few minutes. With the results obtained it is possible to conclude that the use of zirconium as an additive in magnesium alloys has no beneficial effect on absorption. In the other hand, the desorption is extremely attractive. After exposure to air, it was verified that both compositions presented formation of contaminants on the surface and this made the activation a difficult way. However, this effect was more latent in pure magnesium.
Production, structural characterization and properties of hydrogen storage for Mg-Zr alloys
Keywords: Solidificação rápida; Laminação a frio; Ligas de magnésio; Rapid solidification; Cold rolling; Magnesium alloys; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA